Potential MGPB In Optimizing Paddy Straw Mushroom (Volvariella volvacea WW-08) Growth - WINDI SILVANI JEMSI; I NYOMAN PUGEG ARYANTHA (Microbiology Indonesia, 2017)
Paddy straw mushroom (Volvariella volvacea) contains high protein content and delicious flavor, makes it highly demand each year. Production of V.volvacea does not merit the requirements due to its limited production. Therefore, approach in increasing production using mushroom growth promoting bacteria (MGPB) are needed. This study aims to obtain MGPB isolate as potential agent to increase V. volvacea strain WW-08 growth. This is experimental research in laboratory that consisted of indigenous bacteria isolation, MGPB screening with dual culture, MGPB inoculum optimization, molecular identification of selected MGPB using 16S rRNA, protein profiling with SDS-PAGE, and fruting body production. Indigenous bacteria obtained from growth medium were 58 isolate, and W34 bacteria at concentration of 106 sel/ml showed most significant result on micellium growth. Sequence of 16S rRNA region showed W34 bacteria is Bacillus cereus. Visualization of SDS-PAGE showed new protein in result of interaction between Bacillus cereus and V. volvacea strain WW-08 with molecule weight of 17kDa. Average of fruting body of V. volvacea strain WW-08 in treatment of B. cereus harvested for 7 days, was 240.19g, whereas without treatment of B. cereus was 82.15g. These findings indicate treatement of B. cereus strain W34 increase V. volvacea WW-08 growth by 300%.